Perceived effectiveness of agricultural information channels (AIC) in marketing of poultry eggs in Ijebu north-east local government area of Ogun state (2014)
The productivity of the poultry industry like any other industry is hinged on adequate dissemination of information through appropriate channels. This study assessed the perceived effectiveness of agricultural information channels in marketing of poultry eggs in Ijebu North East local government area of Ogun state. Fifty four randomly selected poultry farmers and an equal number of purposively selected marketers were administered with questionnaires. Data on socioeconomic characteristics, availability and extent of use of AIC as well as perceived effectiveness of the channels were collected and analysed. Results showed that more of the farmers were male (81.7%) compared to the marketers, majority of the respondents had formal education (91.7%) and had over five years of experience in their trades (94.4 and 90.7%). Mobile phone was the most readily available and utilised AIC (97.2% and ẋ = 1.46) while the presence of extension agents was not very pronounced (62.0% and ẋ = 0.73). Inconsistent power supply (ẋ=1.52) was the most limiting constraint to the use of the AIC. There was significant difference in the perceived effectiveness of AIC among poultry farmers and marketers (t=3.833, p≤0.005). Sustained use of preferred channels of information was thus advocated while extension agents were urged to step up their activities.